1964
DOI: 10.1002/bip.1964.360020110
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of γ‐ethyl‐L‐glutamate‐N‐carboxyanhydride initiated by di‐n‐butyl and di‐isopropyl amine

Abstract: SynopsisThe yethyl-bglutamate NCA polymerization initiated by di-n-butyl and di-isopropyl amine was studied. The experimental kinetic curves show an autocatalytic portion with 2530% conversion, followed by a pseudo first-order region which extends up to at least 8590%. In this linear region, the reaction order appears to be 0.5 in initiator with both aminea. High degrees of polymerization and high reaction rates were observed. These results are similar to those obtained in the 7-benzyl-cglutamate NCA polymeriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

1965
1965
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…This behavior has been observed for the synthesis of polyL-lysine, poly(γ-benzyl-L-glutamate) (PBLG) and poly(γ-ethyl-L-glutamate) homopolymers using different initiators including DEA 55 61 .…”
Section: Resultsmentioning
confidence: 63%
“…This behavior has been observed for the synthesis of polyL-lysine, poly(γ-benzyl-L-glutamate) (PBLG) and poly(γ-ethyl-L-glutamate) homopolymers using different initiators including DEA 55 61 .…”
Section: Resultsmentioning
confidence: 63%
“…As a secondary amine, HMDS can either function as nucleophile to open the NCA ring at C 5 , or act as a base to deprotonate the NH group [11]. Previous studies showed that secondary amines with bulky alkyl groups (e.g., diisopropylamine) exclusively deprotonated NCAs [38]. Therefore, it is unlikely that HMDS, a secondary amine containing two bulky TMS groups, attacks the C 5 of Bn-Glu NCA.…”
Section: Recent Developmentsmentioning
confidence: 99%
“…11 Previous studies showed that secondary amines with bulky alkyl groups (e.g., diisopropylamine) exclusively deprotonated NCAs. 13 Therefore, it was unlikely that HMDS, a secondary amine containing two bulky TMS groups, attacked the CO-5 of Glu-NCA (Scheme 1). If the first step involved the deprotonation of the NH-3 proton of NCA by HMDS, an N-TMS NCA would form and should undergo rapid rearrangement to form R-isocyanatocarboxylic acid TMS esters.…”
mentioning
confidence: 99%